KAPABILITAS PEMERINTAH KABUPATEN BOYOLALI DALAM PROGRAM SISTER VILLAGE SEBAGAI UPAYA MITIGASI BENCANA ERUPSI GUNUNG MERAPI - Putri, Shinta Noor Aini; Hanani, Retna; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2024)
Local government capability in disaster management is something that must be prioritized. Boyolali Regency is crossed by Mount Merapi, disaster mitigation is needed to minimize loss of life due to the eruption of Mount Merapi. BPBD Boyolali designed a Sister Village strategy or sibling villages to anticipate the threat of Mount Merapi. Sister Village in Boyolali developed the Boyolali BPBD by imitating the Magelang Regency BPBD which has implemented Sister Village. The poor logistics information system and the absence of a special budget for this program are the reasons for the importance of this research. This research aims to analyze the capabilities of the Boyolali Regency Government in the Sister Village program as an effort to mitigate the disaster of the eruption of Mount Merapi. This research uses a qualitative descriptive method by collecting data through observation, interviews and documentation. The results of the research show that the institutional capabilities of Boyolali Regency in the Sister Village program have clarity in organizational tasks and functions. The human resource capability in implementing the formation of Sister Village has a sufficient number of personnel. Capability policies are seen from existing policies. Budget capability is still not optimal, seen from the lack of a Sister Village program budget. Technical capabilities can be seen from technical evacuation maps, logistics management but the information system is still simple. Leadership capabilities can be seen from the ongoing coordination and command functions. The government must develop information systems to make them more easily accessible.